Level of motivation, self-confidence, anxiety control, mental preparation, team cohesiveness and concentration of elite and non-elite athletes - Ita, S.; Kardi, I. S.; Hasan, B.; Nurhidayah, D. (Journal of Physical Education and Sport, 2022)
The level of psychological skills of athletes affects the achievement of sports achievements. This study aims to look at the level of psychological skills of elite and non-elite athletes including motivation, self-confidence, anxiety control, mental preparation, team cohesiveness and concentration. This research was quantitative, descriptive, with a cross-sectional design. The population in this study included a total of 534 athletes. For the sample, we used the simple purposive sampling technique to obtain a sample of 90 athletes consisting of 30 elite athletes and 60 non-elite athletes with an age range of 17 - 35 years consisting of 54 male athletes and 35 female athletes. Athletes come from athletics (sprint, long jump, middle distance running and long distance running), swimming, triathlon, weightlifting, bicycle racing (road race and track), and rowing (TBR and canoeing). Data collection techniques involving the psychological skills inventory for sports. The results showed that elite athletes had a "very high" level of psychological skill with a "very high" level of motivation, "very high" self-confidence, "very high" anxiety control, "very high" mental preparation, "very high" team cohesiveness, and "very high" concentrations. While non-elite athletes have a "high" level of psychological skill with a "very high" level of motivation, "high" self-confidence, "high" anxiety control, "high" mental preparation, "high" team cohesiveness, and "high" concentration. Based on the results of the Z test, the sig (2 tiled) value was 0.000<0.05, so it can be concluded that there is a significant difference between the psychological skill levels of elite and non-elite athletes in Indonesia.